HUBUNGAN ANTARA BEBAN KERJA DAN DUKUNGAN SOSIAL REKAN KERJA DENGAN PRESENTEEISM PADA PERAWAT - Wulandari, Putri; Aprilia, Nugraini (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
This study aims to examine the relationship between workload and coworker social support with presenteeism among nurses. A correlational quantitative approach was used with 115 nurse participants working in hospitals, clinics, community health centers, and home care services in Kudus, Pati, and Demak. The sampling technique applied was purposive sampling with a minimum one-year work experience requirement. The instruments consisted of three psychological scales: presenteeism, workload, and coworker social support all of which passed validity and reliability testing. Data were analyzed using Pearson product-moment correlation and multiple linear regression. The results showed a significant positive correlation between workload and presenteeism(r = 0.471, p less than 0.01) and a significant negative correlation between coworker social support and presenteeism (r = –0.385, p less than 0.01). Furthermore, regression analysis indicated that workload and coworker social support jointly contributed significantly to presenteeism (R squared = 0.294, F = 23.335, p less than 0.01). These findings emphasize the importance of managing workload and strengthening coworker support to reduce presenteeism among nurses.